The peculiarities of physical conditioning level testing of American schoolchildren (state of Missouri) - Мандюк [Mandiuk A.], А. Б.; Чухраюк [Chuhraiuk A.], А. О. (Slobozhanskyi Herald of Science and Sport, 2012)
The article looks at the peculiarities of physical conditioning level testing of American pupils. According to the results of special normative documentation analysis, the significance and peculiarities of physical conditioning level testing in American physical education system were determined. The article offers standards which schoolchildren in the USA, depending on their age and sex, should qualify. As a result of the research some typical exercises, which are used in the process of physical conditioning level testing, were distinguished.